Development of Indigenous Language Orthographies: Setting Up English as the Torch Bearer - Juniel Shoko Matavire (International Journal of Critical Diversity Studies)
The argument that Indigenous languages require revitalisation through more pronounced roles across the fabric of society remain a social justice and affirmative action issue since 1994. The need for language development remains a remnant of the liberation project that commenced with the dawn of freedom in 1994. While political freedom and other liberties were obtained, Indigenous languages remained under the chokehold of English and Afrikaans. Arguments have pointed to a lack of zeal on the part of the government of South Africa to deliberately promote, develop and intellectualise Indigenous languages, but the element of strategy for implementation appears to have been forgotten in the tracks. What has remained unclear are the strategies to develop and intellectualise Indigenous languages. Such strategies have to accommodate the multilateral issues of social, economic, cultural, racial and linguistic diversity in the country. What appears fuzzy is the role that international, developed and economically strong languages such as English have in this endeavor. From an orthographic depth hypothesis point of view, this literature paper posits that Indigenous languages stand to gain extensively from a terminological, lexical and pragmatic association with multinational languages. A deliberate approach is required to understand the trajectories followed by already developed languages and the lessons that can be drawn from them in implementing standardization and revitalisation of Indigenous languages. Such torch bearer role of English can assist in harnessing the benefits that extend to advancing the national thrust towards inclusivity in diversity and meeting constitutional obligations in parity of esteem.